Analyzing the Impact of Foreign Board and Foreign Ownership on Dividend Policy: Evidence from Indonesia - Rafie Akbar Sumarno; Muhammad Husni; Anto Andreawan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Dividend policy is crucial for the company because there are investors who are entitled to and await cash dividends distributed by the company. However, on the other hand, management believes that the company's profits are better retained for the purpose of future investments. Indonesia adopts a two-tier system for board members in companies by separating the supervisory function of the board from the executive function of the board. The purposive sampling technique was used in the selection of research samples, resulting in 543 companies during the years 2018-2021. The results of the panel data regression using the Lagrange Multiplier test obtained REM as the best model. with the results of Foreign Directors having a significant and positive impact on dividends, as well as the results of Foreign Commissioners having a significant and positive impact on dividends, then foreign ownership has a negative and significant impact on dividends